OPTIMIZING CAREER SELF-EFFICACY THROUGH ACADEMIC ABILITY TEST- BASED GUIDANCE SERVICES FOR SENIOR HIGH SCHOOL - Ach. Firman Ilahi; Azzahro Afaf Syamilah Via Ramadani; Ach. Ubaidillah Al Jazili (Fakultas Dakwah dan Ushuluddin Universitas Ibrahimy, 2026)
Career-determining path represents a critical developmental stage for final-year high school students. At this stage, they are required to make important decisions that will influence their future educational and career trajectories. Nevertheless, many students experience uncertainty and confusion due to an insufficient understanding of their own potential, interests, and abilities.. This study aims to analyze the implementation of career guidance and counseling (BK) services, the utilization of Academic Ability Test (TKA) results, students’ career self-efficacy levels, and efforts to optimize TKA-based career guidance and counseling services at State High School 1 Prajekan Bondowoso. The study employed a descriptive qualitative approach. The results indicate that the guidance and counseling services have been running well and have gained students’ trust; however, career guidance and counseling services remain general in nature and are not yet systematically based on academic data. The utilization of TKA results is also not yet optimal because they are used primarily for administrative purposes. In addition, students’ career self-efficacy still varies due to internal and external factors. These findings indicate that integrating the TKA into career guidance and counseling services can contribute to improving students’ career self-efficacy.